Patented and Generic Pharmaceutical Drugs: Perception and Prescription - Ernest Cyril, de Run; Mee-Kon, Ng Felix (Universiti Malaysia Sarawak (UNIMAS), 2006)
This research aims to determine perceptions of doctors under the employ of the government in Sarawak towards patented drugs and generic drugs. It also sets out to determine factors that affect doctors’ prescribing decisions. The population consists of all the doctors working in the Sarawak government hospitals. This research utilizes both qualitative (interview) and quantitative (questionnaire) methods in obtaining data. Data from the interviews was analyzed and then placed in a questionnaire format. This was then analyzed using Factor analysis. Findings indicate that doctors have different perceptions towards patented and generic drugs and consider several factors in prescribing drugs.